Differences in reading preferences of preservice teachers according to frequent reading language (Galician and Spanish) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2024)
Knowing the reading preferences of preservice teachers is essential due to their key role as trainers of readers. This study analyzes the reading preferences of students in the Early Childhood and Primary Education degrees according to the language in which they prefer to read (Galician or Spanish), taking into account the typologies, genres and subgenres of the selected literary works. The results show that, although there is a predominance of works in Spanish, in Galician we find a greater variety of genres and discoursive subgenres. The need to promote reading in Galician and to improve the literary training of preservice teachers is highlighted.
Keywords: reading; reading preferences; preservice teachers; minoritized languages; reading interests